Chasing the culprit in shadow – Sinonasal mucormycosis in an immunocompetent host. (October 2021) - Singh, Anup; Choudhary, Ishan; Handa, Aru C
Rhino-orbital mucormycosis is an uncommon, rapidly progressive, fulminant, angio-invasive deep mycosis usually affecting individuals with underlying immunosuppression, the most common being diabetes mellitus. In such, the course may be fatal with dissemination. Early detection with control of underlying predisposing conditions is critical with respect to the prognosis. Rarely, mucormycosis may develop in an immunocompetent host, when its non-specific symptomatology and inconspicuous radiological findings may obscure its diagnosis. Any delay in treatment predisposes to multi-organ morbidity and potential mortality. We present an immunocompetent adult with no underlying predisposing illness who was harbouring invasive sinonasal mucormycosis causing orbital cellulitis. A high index of suspicion is mandatory.